Keratoacanthoma Accompanied by Multiple Lung Squamous Cell Carcinomas Developing in a Renal Transplant Recipient - Furudate, Sadanori (S. Karger AG, 2014)
Keratoacanthoma (KA) is a benign keratinocytic neoplasm that spontaneously regresses after 3–6 months and shares features with well-differentiated squamous cell carcinoma (SCC). An increased incidence of both KA and non-melanoma skin tumor, including SCC, is seen among immunosuppressed, organ-transplant recipients. In this report we describe a case of KA accompanied by multiple lung SCCs developing in a renal transplant recipient.